ChemInform Abstract: Organocatalyzed Asymmetric Synthesis of Morphans. Issue 37 (22nd August 2013) - Bradshaw, Ben; Parra, Claudio; Bonjoch, Josep
Abstract For the first time an effective organocatalytic synthesis of polyfunctionalized enantiopure morphans is developed.